Vitamin D Decreases Susceptibility of CD4+ T Cells to HIV Infection by Reducing AKT Phosphorylation and Glucose Uptake: A Bioinformatic and In Vitro Approach - John D. Loaiza; Jose Fernando Gómez; Daniel Muñoz-Escudero; Sandra M. Gonzalez; Timothy Kyle Eubank; Maria T. Rugeles; Ana Lucía Rodríguez-Perea; Wbeimar Aguilar-Jimenez (Biomolecules)
Activated immune cells are highly susceptible to human immunodeficiency virus (HIV) infection. Vitamin D (VitD) induces antimicrobial responses and reduces cellular activation. We investigated VitD effects on HIV-1 replication, glucose uptake, and gene regulation using computational and in vitro approaches. CD4+ T cells from healthy male donors were treated with VitD and infected with HIV-1. After 72 h, p24 protein was measured to assess viral replication. VitD effects on anti- and pro-HIV genes were analyzed by a Boolean network model based on curated databases and the literature. CCR5 and CXCR4 coreceptor expression, AKT phosphorylation, and glucose uptake were evaluated by flow cytometry, and expression of some model-identified genes was quantified by qPCR. VitD reduced p24 by 53.2% (p = 0.0078). Boolean network modeling predicted that VitD upregulates antiviral, migration, and cell-differentiation related genes, while downregulating genes related to cellular activation, proliferation, glucose metabolism, and HIV replication, notably AKT1, CCNT1, SLC2A1, HIF1A, and PFKL. In vitro, VitD reduced AKT phosphorylation by 26.6% (p = 0.0156), transcription of CCNT1 by 22.7% (p = 0.0391), and glucose uptake by 22.8% (p = 0.0039) without affecting classic antiviral genes or coreceptor expression. These findings suggest an anti-HIV effect of VitD, mediated through AKT and glucose metabolism downmodulation, both involved in cell activation and HIV-1 replication.